Interventions for preventing weight gain after smoking cessation - Shraim, M; Parsons, A; Aveyard, P; Hajek, P (2006)
This is the protocol for a review and there is no abstract. The objectives are as follows: The primary objective is to review the evidence from two kinds of trials: (i) The effects of interventions specifically designed to limit weight gain on two outcomes: weight gain and smoking cessation. (ii) The effects of antidepressants, nicotine replacement therapy and exercise interventions on weight gain. For weight gain in (i) and (ii), the effects will be examined only in those with sustained abstinence from smoking. Secondary ojectives include: (i) The effects of the interventions on weight gain and smoking cessation at the end of the programme and at least six months postcessation, to determine whether any effects on weight gain and cessation are temporary. (ii) To examine evidence of interactions between body characteristics, gender, and psychological variables such as fear of weight gain on (a) smoking cessation and (b) weight gain. Copyright © 2006 The Cochrane Collaboration. Published by John Wiley and Sons, Ltd.